Alpha-linolenic acid reshapes the gastrointestinal ecology to enhance immune function in dairy cows: insights from microbiome and metabolome profiling - Ji, Hongjin; Yang, Zhantao; Hao, Yangyi; Wang, Yajing; Cao, Zhijun; Yang, Hongjian; Wang, Wei; Li, Shengli (Frontiers in Microbiology, 2025)
IntroductionAlpha-linolenic acid (ALA), an essential polyunsaturated fatty acid, modulates gastrointestinal microbiota and host immunity, yet its regulatory mechanisms in dairy cows remain unclear.MethodsThis study investigated how dietary ALA influenced gut microbiota, metabolome, and immune function in lactating Holstein cows. Ten cows were randomly assigned to two groups (n = 5) receiving either a low-ALA (LALA, 5.02 ± 0.09% ALA of total fatty acids) or high-ALA diet (HALA, 32.04 ± 1.55% ALA of total fatty acids). Rumen fluid, feces, and blood samples were analyzed post-intervention.ResultsThe HALA group exhibited increased ruminal abundance of Eubacterium coprostanoligenes group and Ruminococcus (p < 0.05), alongside reduced proinflammatory metabolites including dodecanoic acid, myristic acid, and prostaglandin I2 in the rumen. Plasma leukotriene C4 levels were also decreased (p < 0.05). Metabolomic enrichment analysis revealed significant downregulation of arachidonic acid metabolism. Correlation analyses demonstrated that Eubacterium coprostanoligenes group negatively associated with suppressed prostaglandin I2 (rumen metabolite) and leukotriene C4 (plasma metabolite), but positively correlated with enriched fecal Clostridia UCG-014 and Ruminococcus.DiscussionThese findings indicate that high dietary ALA reshapes gastrointestinal microbiota and attenuates inflammatory responses by inhibiting microbial-metabolite-driven arachidonic acid metabolism, thereby enhancing immune regulation in dairy cows.